The last of the blonde bombshells HBO Films presents in association with the BBC and Universal Television ; a Working Title TV Production ; produced by Su Armstrong ; directed by Gillies Mackinnon ; screenplay by Alan Plater. [videorecording] (2010)
Summary goes here